A novel small open reading frame gene, IbEGF, enhances drought tolerance in transgenic sweet potato - Zhou, Yuanyuan; Zhai, Hong; Xing, Shihan; Wei, Zihao; He, Shaozhen; Zhang, Huan; Gao, Shaopei; Zhao, Ning; Liu, Qingchang (Frontiers in Plant Science, 2022)
Small open reading frames (sORFs) can encode functional polypeptides or act as cis-translational regulators in stress responses in eukaryotes. Their number and potential importance have only recently become clear in plants. In this study, we identified a novel sORF gene in sweetpotato, IbEGF, which encoded the 83-amino acid polypeptide containing an EGF_CA domain. The expression of IbEGF was induced by PEG6000, H2O2, abscisic acid (ABA), methyl-jasmonate (MeJA) and brassinosteroid (BR). The IbEGF protein was localized to the nucleus and cell membrane. Under drought stress, overexpression of IbEGF enhanced drought tolerance, promoted the accumulation of ABA, MeJA, BR and proline and upregulated the genes encoding superoxide dismutase (SOD), catalase (CAT) and peroxidase (POD) in transgenic sweetpotato. The IbEGF protein was found to interact with IbCOP9-5α, a regulator in the phytohormone signalling pathways. These results suggest that IbEGF interacting with IbCOP9-5α enhances drought tolerance by regulating phytohormone signalling pathways, increasing proline accumulation and further activating reactive oxygen species (ROS) scavenging system in transgenic sweetpotato.